HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN KECEMASAN MENGHADAPI DUNIA KERJA PADA MAHASISWA TINGKAT AKHIR DI FAKULTAS FARMASI DAN ILMU KESEHATAN UNIVERSITAS SARI MUTIARA INDONESIA - Indo Mora; Siska Dwi Ningsih; Laksana Tobing; Ensina Nuriasi Simarmata (JURNAL PSYCHOMUTIARA, 2020)
This study aims to determine the relationship between social support and anxiety to face the world of work at the final level students. The hypothesis proposed is the existence of a negative relationship between, social support with anxiety facing the world of work at the final level students. The subjecks in this study were as many as 100 final year students in the Faculty of Pharmacy and Health Sciences. The sampling technique in this study was the proportionate stratified random sampling technique used because the population had members/ elements that were homogeneous and proportionately proportional. The measuring instrument used in this study is the scale of social support and scale of anxiety facing the world of work, based on the validity and reliability on the scale of social support obtained 49 valid items with Alpha Cronbach reliability coefficient if the Alpha value >0.60 reliable. Obtained 14 valid items with Alpha Cronbach realibility coefficient if the Alpha value >0.60 reliabel data analysis method used is a statistical method using Paerson Product Moment.Significance value is 0.369 if Sig 0.05 the data meets linear. Based on the result of hypothesis testing, it can be seen that the hypothesis tested in this study was accepted. Thus, it can be concluded that there is a significant, and negative, relationship between social support and anxiety the world of work at the final level students.